ACCELERATED AGEING ASSESSMENT OF BITUMEN AS A PRESERVATIVE FOR THE TREATMENT OF Gmelina arborea WOOD - Jacob Mayowa OWOYEMI; Olasunkanmi Joshua OGUNNIYI (Journal of Applied Life Sciences and Environment, 2023)
Concerns about the health and environmental risks linked with the use of preservatives, such as chromate copper arsenate (CCA), zinc chloride, mercuric chloride, and the oil-born preservative creosote, prompted the quest for the use of readily available bitumen as a wood preservative. Using samples that had been processed into dimensions of 20 × 20 × 60 mm, the durability and physical characteristics of Gmelina arborea wood treated with bitumen were evaluated. The samples were dried for 24 hours in an oven set to 103°C and treated with hot bitumen at a melting point of 270°C to ensure the flow and maximum penetration of the bitumen. The density showed mean values of 504.93 and 498.71 kg/m3 for the untreated and treated samples, respectively, with the treated samples recording lower values due to the thermal difference in the density distribution between the untreated and treated wood samples. The average weight loss due to leaching of the untreated and treated wood samples after soaking in cold water and hot water was 3.07% and 0.07%, 1.49% and 1.38% respectively for the treatment. The study confirmed the suitability of using bitumen as a preservative for treating G. arborea wood in an environment with extreme weather conditions without causing serious leaching, thereby exposing the wood to degrading agents.